Optimalisasi Kualitas Pelayanan di Kantor Kecamatan: Sebuah Studi tentang Efisiensi dan Kepuasan Masyarakat - M. Harry Mulya Zein; Sisca Septiani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2020)
This study aims to examine the quality of public services in Pusakajaya District, Subang Regency, focusing on citizens' basic needs and civil rights. This study used qualitative and descriptive methods, with data collected through interviews and observations. Data analysis is done through data reduction, presentation, and conclusions. The results showed that the quality of service at the Pusakajaya sub-district office was not satisfactory, mainly due to limited physical infrastructure and service facilities, such as the absence of a comfortable waiting room, inadequate service room, and lack of air conditioning facilities. Despite these barriers, service processes generally conform to existing standards. Supporting factors for service quality are employee work motivation while inhibiting factors include employee shortages and inadequate infrastructure. This study suggests improvements in human resource management, acceleration of infrastructure development, and increased employee motivation as important steps to improve service quality. It is hoped that with this improvement, the quality of service in Pusakajaya District can meet the needs and expectations of the community more effectively.